The Effectiveness Of Ariel Noah Representation As Gojek's Brand Ambassador For Gojek's Social Media - Rindina Hundura; Silfia Silfia; Zubyan Chaudhary (Publikasi Indonesia, 2023)
In addition to analyzing the relationship between age, gender, and frequency of use of the Gojek application in the user's perception of Ariel Noah as the Gojek application brand ambassador, this study aims to describe the percentage of respondents' positive responses to Ariel Noah as the brand ambassador of the Gojek application. A total of 300 respondents were chosen at random to complete an online survey. Data were descriptively analyzed to determine the percentage of respondents who thought favorably of Ariel Noah as the brand ambassador for the Gojek application and to examine the relationship between age, gender, and frequency of Gojek usage in users' opinions of Ariel Noah as the application's brand ambassador. The findings revealed that 77% of the respondents were interested in Ariel Noah's role as a Gojek brand ambassador and had a favorable opinion of his ability to promote Gojek services. The results of the chi-square correlation test indicated that the factors of age, gender, and frequency of application use were significant at 0.561, 0.485, and 0.000, respectively. The conclusion that can be drawn from this research is that 77% of respondents have an interest in and a positive view of Ariel Noah as a Gojek brand ambassador and his influence in promoting Gojek services. In the Chi-square test, it was found that there was no relationship between the age and gender variables on the views of Ariel Noah's users as the brand ambassador for the Gojek application. There is a relationship between the frequency of using the application and the views of users of Ariel Noah as the brand ambassador for the Gojek application.